Decomposition Analysis of Energy Consumption in Thailand, 1990-2020 - Tippichai, Atit (International Journal of Energy Economics and Policy, 2022)
Thailand is a net energy importer that has steadily increased the demand for energy over the past several decades. But there has not been a systematic analysis of the energy demand change factors. Therefore, a decomposition analysis was applied to determine the major factor causing the change in energy use during the years 1990-2020. The analysis covered a regional financial crisis known in Thailand as the “Tom Yum Kung” crisis in 1997-1998 and a global pandemic COVID-19 in 2020 onwards. The analysis results showed that the value-added of economic sectors is the most important factor with requiring more energy, while energy intensity is the second most important factor in reducing energy consumption. Therefore, increasing the value-added of productions and enhancing the energy efficiency more stringent will lead to a decoupling of energy consumption against GDP and a sooner peak demand of energy in Thailand.